Concerns about Lycan's commonsensism. (3rd September 2022) - Bergmann, Michael
Abstract: Despite wholeheartedly endorsing Lycan's commonsensism on display in On Evidence in Philosophy, this paper raises concerns about three views Lycan defends in that book. The first view is compatibilism about free will and determinism. The paper argues that Lycan's Moorean defense of compatibilism fails and that it is plausible for commonsensists to think that, in their dispute with incompatibilists, the burden of proof is on compatibilists. The second view is Lycan's Principle of Humility, offered as an account of the conditions under which recognized disagreement undermines knowledge. The paper considers a permissive and a demanding way of understanding his Principle of Humility and suggests that, contra Lycan, commonsensism fits better with a permissive understanding. The third view discussed is his coherentism about justification. The paper concludes that commonsensism is best understood in foundationalist terms and that Lycan's coherentism is, in fact, an inadequately motivated version of foundationalism.